Nanostructured Materials for the Detection of CBRN (NATO Science for Peace and Security Series A: Chemistry and Biology,, 2018)
This book includes topics in nanophysics, nanotechnology, nanomaterials, sensors, biosensors, security systems, and CBRN agents detection. There have been many significant advances in the past two years and some entirely new directions of research are just opening up. Recent developments in nanotechnology and measurement techniques now allow experimental investigation of the physical properties of nanostructured materials. The book presents new methods for the detection of chemical, biological, radiological and nuclear (CBRN) agents using chemical and biochemical sensors. Identification, protection and decontamination are the main scientific and technological responses for the modern challenges of CBRN agents.